Electrical resistivity reduction with pitch-based carbon fiber into multi-walled carbon nanotube (MWCNT)-embedded cement composites. (20th March 2018) - Park, Hyeong Min; Kim, G.M.; Lee, Sol Yi; Jeon, Haemin; Kim, Seong Yun; Kim, Minkook; Kim, Jae Woo; Jung, Yong Chae; Yang, B.J.
Highlights: Electrically conductive cement composites containing MWCNT and CF were prepared. Test specimens with various CF length, filler content, and w/c ratio were fabricated. The incorporation of CF into the MWCNT-embedded composite causes the bridge effect. The improved electrical and viscous properties of proposed composites was observed. Abstract: Recently, various functional construction materials based on carbon nanotubes (CNTs) are being researched; however, there are very few examples of practical use due to cost and workability obstacles. In order to overcome these limitations, we studied the electrical characteristics of multi-phase cement composites containing multi-walled carbon nanotubes (MWCNTs) and economical pitch-based carbon fiber (CF). Test specimens with various formulations of the CF length, content, and water/cement (w/c) ratio are manufactured and their properties are evaluated. The pitch-based CFs used in the experiments were analyzed by Raman spectroscopy and X-ray photoelectron spectroscopy (XPS). The resistance of the conductive cement composites was measured by a two-probe method, and the viscosity was evaluated using a rheometer immediately after the mixing process. In addition, the internal structure of the specimens was analyzed using a scanning electron microscope (SEM) and by micro-computed tomography (Micro-CT) analyses. It was observed that the incorporation of CFs into the CNT-embedded cement composite causes the CFs to serve as a bridge between CNT particles, thus maintaining the homogeneity of the conductive network in the composites. In addition, although an increase of the w/c ratio improved the viscosity of the composites by 90%, the electrical resistivity was retained due to the bridging effect of the CF.